Gene-enriched draft genome of the cattle tick Rhipicephalus microplus: assembly by the hybrid Pacific Biosciences/Illumina approach enabled analysis of the highly repetitive genome. Issue 9 (August 2017) - Barrero, Roberto A.; Guerrero, Felix D.; Black, Michael; McCooke, John; Chapman, Brett; Schilkey, Faye; Pérez de León, Adalberto A.; Miller, Robert J.; Bruns, Sara; Dobry, Jason; Mikhaylenko, Galina; Stormo, Keith; et al.
Graphical abstract: Highlights: Pac Bio/Illumina hybrid assembly of the 7.1 Gbp cattle tick Rhipicephalus microplus genome. The genomic loci for 24, 758 protein-coding transcripts were identified. 191 microRNAs, of which 23 represent novel microRNA families, were found. The novel cytochrome CYP41 gene may associate with acaricide resistance. Abstract: The genome of the cattle tick Rhipicephalus microplus, an ectoparasite with global distribution, is estimated to be 7.1 Gbp in length and consists of approximately 70% repetitive DNA. We report the draft assembly of a tick genome that utilized a hybrid sequencing and assembly approach to capture the repetitive fractions of the genome. Our hybrid approach produced an assembly consisting of 2.0 Gbp represented in 195, 170 scaffolds with a N50 of 60, 284 bp. The Rmi v2.0 assembly is 51.46% repetitive with a large fraction of unclassified repeats, short interspersed elements, long interspersed elements and long terminal repeats. We identified 38, 827 putative R. microplus gene loci, of which 24, 758 were protein coding genes (≥100 amino acids). OrthoMCL comparative analysis against 11 selected species including insects and vertebrates identified 10, 835 and 3, 423 protein coding gene loci that are unique to R. microplus or common to both R. microplus and Ixodes scapularis ticks, respectively. We identified 191 microRNA loci, of which 168 have similarity to known miRNAs and 23 represent novel miRNA families. We identified the genomic loci of several highly divergent R. microplus esterases with sequence similarity to acetylcholinesterase. Additionally we report the finding of a novel cytochrome P450 CYP41 homolog that shows similar protein folding structures to known CYP41 proteins known to be involved in acaricide resistance.